1998
DOI: 10.1002/pro.5560070312
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of human DNase I at the DNA binding interface: Implications for DNA recognition, catalysis, and metal ion dependence

Abstract: Human deoxyribonuclease I (DNase I), an enzyme used to treat cystic fibrosis patients, has been systematically analyzed by site-directed mutagenesis of residues at the DNA binding interface. Crystal structures of bovine DNase I complexed with two different oligonucleotides have implicated the participation of over 20 amino acids in catalysis or DNA recognition. These residues have been classified into four groups based on the characterization of over 80 human DNase I variants. Mutations at any of the four cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 34 publications
11
86
0
3
Order By: Relevance
“…It seems plausible that the appearance of the new Cys residue distal from the essential Cys residues at the C-terminal end of the protein might not affect formation of the normal disulfide bond. Pan et al [35] have proposed that the amino acid residues in the DNase I protein be classified into four groups based on their different function roles; the first, second, third and fourth classes are composed of the four residues absolutely essential for catalysis, the three crucial acidic residues serving as ligands for metal ion chelation, the seven residues critically involved in DNA-interacting positions encircling the active site, and the 13 residues interacting with DNA distal from the active site, respectively. Among the non-synonymous SNPs in DNASE1 examined, the amino acid residues corresponding to p.Asp190His, and to p.Arg133Gln, p.Arg133Leu and p.Asn192Ile, belong to the second and the third classes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible that the appearance of the new Cys residue distal from the essential Cys residues at the C-terminal end of the protein might not affect formation of the normal disulfide bond. Pan et al [35] have proposed that the amino acid residues in the DNase I protein be classified into four groups based on their different function roles; the first, second, third and fourth classes are composed of the four residues absolutely essential for catalysis, the three crucial acidic residues serving as ligands for metal ion chelation, the seven residues critically involved in DNA-interacting positions encircling the active site, and the 13 residues interacting with DNA distal from the active site, respectively. Among the non-synonymous SNPs in DNASE1 examined, the amino acid residues corresponding to p.Asp190His, and to p.Arg133Gln, p.Arg133Leu and p.Asn192Ile, belong to the second and the third classes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the electrostatic interactions introduced in these variants have a variety of effects on DNase I activity. In addition to increasing the functional catalytic activity by binding to DNA more effectively and being more resistant to inhibition by salt than wild-type DNase I~Pan & Lazarus, 1997, 1998Pan et al, 1998aPan et al, , 1998b! the Class B hyperactive variants are also relatively independent of Ca 2ϩ for their activity.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological and clinical importance of DNase I has led us to engineer hyperactive variants that have a different functional mechanism for DNA cleavage~Pan & Lazarus, 1997, 1998!, as well as actin-resistant variants of DNase I that are no longer inhibited by actin~Ulmer et al, 1996! ; characterization of these variants under biologically relevant ex vivo conditions has shown a marked improvement in potency compared to wild-type~Pan et al, 1998a Structural-functional analysis has implicated several critical DNAcontacting residues surrounding the active site and other DNAinteracting positions that are distal to the active site and contribute less to activity~Jones et al, 1996;Pan et al, 1998b;Evans et al, 1999!. A selected group of amino acids at the DNA binding interface, yet distal to the active site, has been systematically replaced with positively charged residues, yielding hyperactive human DNase I variants that are substantially more active than wild-type under physiological saline conditions~Pan & Lazarus, 1997Lazarus, , 1998 In the present work, we investigated the effect of the Ca 2ϩ ions on the DNA cleavage activity of wild-type human DNase I and its hyperactive variants. Furthermore, we determined the role of the two structural Ca 2ϩ binding sites through site-directed mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This substitution has been reported to decrease WT DNase1 activity by B10-fold. 47 We found that knocking down the activity site resulted in restoration of cell survival ( Figure 5), as well as reduction in the number of apoptotic cells (Figure 8) and chromatin-degrading effect (Figure 7). These findings suggest that C11 and C13 triggered apoptosis by direct cleavage of the genomic DNA through their catalytic site.…”
Section: Discussionmentioning
confidence: 83%